(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Acute on chronic liver failure (ACLF) is defined as acute hepatic insult manifesting as jaundice and coagulopathy complicated within 4 weeks by ascites and/or encephalopathy in a patient with previously diagnosed or undiagnosed chronic liver disease. It has various etiology and manifestations, as well as high mortality. These etiologies vary depending on geographical region - from east to west. For example, infectious etiologies predominate in the east whereas alcohol and drugs constitute the majority of acute insults in west. In Asian region, reactivation of hepatitis B virus and superinfection with hepatitis E virus are more common among the infectious etiologies. Objective: As the incidence of chronic liver disease is increasing day by day and the etiology of acute decompensation of underlying chronic liver disease varies depending on geographical location, so it may be different in Bangladesh from other Asian countries. A very few studies have been published so far showing etiological prevalence of Acute on Chronic Liver Failure (ACLF) in Bangladesh. This study has been conducted to address the etiology of ACLF in our perspective. Methods: A cross sectional longitudinal study carried out in the department of Medicine, Chittagong Medical College Hospital. Thirty patients admitted with ACLF as defined by Asia Pacific Association for Study of Liver Disease (APASL) were consecutively included. Detailed history, complete physical examination and laboratory investigations were done for each patient. 77 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Results: From January 2009 to December 2009, among thirty patients 6 cases (20%) of ACLF was caused by HEV super infection followed by Sepsis (16.67%), variceal bleeding (13.33%) and hepatotoxic drugs (3.33%) respectively. Multiple factors were found in (16.67%) cases while no cause could be identified in (30%) cases. In our study common causes of chronic liver diseases were hepatitis B (50%), hepatitis C (26.67%) and alcohol (16.67%). Among thirty patients five died within forty eight hours of hospital admission. In hospital mortality was 16.67%. Conclusion: Acute on Chronic Liver Failure (ACLF) is one of the commonest causes of mortality, morbidity and socio-economic burden particularly in Bangladesh. Early detection and proper management of acute events that lead to ACLF would alleviate mortality and morbidity. However due to high treatment cost, proper management of chronic liver diseases as well as ACLF cannot be afforded by most people in our country. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21837 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013